PEMBUATAN GAME MOBILE ARCADE “COVID GO AWAY” BER PLATFORM ANDROID - Geovanny Valerian Soemitha; Jeanny Pragantha; Darius Andana Haris (Fakultas Teknologi Informasi Universitas Tarumanagara, 2021)
“Covid Go Away” is an arcade game with a campaign theme. This game is played on Android devices with minimum API Level Android 4.4